2008
DOI: 10.1007/s00421-007-0664-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training increases the stimulated percentage of CD4+CD25+ in older men but not older women

Abstract: The purpose of the present study was to determine whether 12 months of moderate intensity cycling would increase the expression of IL-2 (CD25+) receptors in T helper (CD4+) lymphocytes in men and women aged 65-75 years. Fourteen men and 10 women completed 52 weeks of moderate intensity cycling (60% VO2peak). Subjects trained (TR) three times per week for 45 min per session. Eight age-matched untrained (UT) male and eight UT female subjects acted as controls. Resting blood samples were taken from TR and UT subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The flow cytometer (Epics Profile ll, Coulter, USA) was calibrated as described elsewhere (Broadbent and Gass 2008). Receptor density was measured with mean channel log fluorescence, with [5,000 cells analysed per sample.…”
Section: Flow Cytometric Calibrationmentioning
confidence: 99%
“…The flow cytometer (Epics Profile ll, Coulter, USA) was calibrated as described elsewhere (Broadbent and Gass 2008). Receptor density was measured with mean channel log fluorescence, with [5,000 cells analysed per sample.…”
Section: Flow Cytometric Calibrationmentioning
confidence: 99%
“…These results suggest that physical activity can positively affect immunological factors that usually cause disease progression in HIV 112. Broadbent and Gass113 found that 52 weeks of physical activity increases CD4+ and CD25+ percentages in older men. Another study reported an inverse relationship between regular physical activity and viral load,114 a finding that had not been previously supported in the literature.…”
Section: Physical Activity and Immune Functionmentioning
confidence: 77%
“…Therefore, the increased proportion of KLRG1+ cells among the CD4+ T-cell population during the middle of the training phase could be due to an inXux of regulatory T cells. Indeed, long-term, moderate exercise training increases the frequency of CD4+/CD25+ blood T cells in the elderly (Broadbent and Gass 2008). The impact of regular high-volume exercise training on the frequency and suppressive activities of Treg cells warrants further investigation as this could provide further insight on how high-volume exercise training inXuences immunity in athletic populations.…”
Section: Discussionmentioning
confidence: 98%